Antiplasmodial activity and cytotoxicity of kapur (Harmsiopanax aculeatus) leaf extracts traditionally used for the treatment of malaria in Maluku - Turalely, Rachel; Mustofa; Mahardika Agus Wijayanti; Triana Hertiani (Indonesian Journal of Pharmacology and Therapy, 2020)
Harmsiopanax aculeatus leaf, locally name kapur, has been use traditionally to treat malaria in Maluku, Indonesia. However, the scientific evidences that support its use are still limited. This study aimed to investigate antiplasmodial activity of H. aculeatus leaf extract and its cytotoxicity on cancer cells line. Three extracts i.e. methanolic, n-hexanic and ethyl acetate extracts were evaluated for their in vitro activity against Plasmodium falciparum FCR3 strain using microscopic method. Cytotoxicity of the extracts on T47D, HeLa and Vero cells lines were determined using MTT assay method. The inhibitory concentration 50% (IC50) against P. falciparum or the cells lines growth was determined using probit analysis. Furthermore, their selectivity index (SI) were determined. The results showed that the methanolic extract was the most active extract with an IC50value of 13.82 μg/mL and the most selective with a SI value of 172.84. The three extracts tested exhibited weak or no cytotoxicity against the cells lines used with IC50 values ranged 101-2388.69 μg/mL. Further study will be conducted to isolate active antiplasmodial compounds from the methanol extract.